PENGARUH KARTU DEBIT DAN E-MONEY TERHADAP PENGELUARAN KONSUMTIF MAHASISWA - Muhammad Dian Ruhamak; Rizqiah Novitasari Toatubun; Bothy Dewandaru; Anindhitiya Sofi Melisa; Fadhila Amara Alif Sitoresmi (Juremi: Jurnal Riset Ekonomi, 2023)
The development of financial technology or better known as fintech is currently able to provide convenience in the payment system. Financial Technology (Fintech) can be defined as an industry that uses technology to support the financial system and financial services more effectively and efficiently. With this development, the function of cash that has been used by the community as a transaction tool has shifted to non-cash transactions, with this non-cash payment system making it easier for people, especially students, to make transactions, such as Debit Cards and E-Money such as OVO, Gopay, DANA, Shoopepay, Brimo. The purpose of this study was to determine the effect of Debit Cards and E-Money on consumptive spending of Kadiri University students. The sample used in this study were 58 respondents, in this study using a quantitative approach. The data analysis techniques used are validity and reliability tests, multiple linear regression analysis tests, and hypothesis testing (t-test) and the coefficient of determination (R2) test. Based on the results of testing the Debit Card variable partially has a significant effect on consumptive spending, and the results of the E-Money variable test partially have a significant effect on consumptive spending, while simultaneously, the Debit Card variable, E-Money has a positive effect on student consumptive spending